Penyuluhan dan Pendampingan Pemasaran Media Sosial dan Optimalisasi Fasilitas Produksi Tahu-Tempe di Kekalik Gerisak Mataram - Sulhaini; Sulaimiah; Yusron Saadi; Fathmah Mahmud (Universitas Mataram, 2026)
Based on the results of the service activities organized by the previous team, it is known that tofu tempeh business actors in the Kekalik Grisak environment, Kekalik Jaya Village, Sekarbela District, Madya Mataram City, NTB have not utilized digital technology in marketing their products. In addition, they still use simple methods and facilities in producing tofu-tempeh. Therefore, this service activity focuses on counseling and assistance in improving business actors' marketing capabilities by using social media and optimizing production facilities. The activity was held in a prayer room in the Kekalik Grisak neighborhood; the entrepreneurs were contacted one week beforehand. However, the team approached entrepreneurs through local youth leaders. There were 10 participants who participated in the counseling, and the team also assisted by visiting their production sites. From this service activity, participants gained an understanding of how to use social media to market products and improve production facilities. Meanwhile, the team also identified various obstacles faced by business actors that can be the focus of future service activities.